Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140035
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Thyroid System in Myelination and Neural Connectivity

Abstract: The role of thyroid hormone on brain development is dramatically illustrated by "cretinism," a severe mental retardation due to iodine deficiency and maternal hypothyroidism during gestation. In the last decades, the molecular bases of the cellular action of thyroid hormone in the nervous tissue have been at least partially elucidated, and the emerged picture is much more complex than expected. In this article, the main mechanisms determining thyroid hormone availability, nuclear and membrane receptor occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 213 publications
0
29
1
Order By: Relevance
“…These data supported the attempt to use TH to overcome OPCs differentiation block during experimental inflammatory‐demyelinating diseases. Our previous work showed that a short in vivo TH administration during experimental allergic encephalomyelitis (EAE) promotes OPCs maturation, protects myelin sheaths and axons, and ultimately improves functional and clinical outcome in rat and non‐human primates Callithrix Jacchus (Calzà et al, ; Dell'Acqua et al, ; D'Intino et al, ; Fernández et al, ). TH supplementation also restores oligodendroglial lineage and OL maturation from neural stem/progenitor cells (NSCs) derived from inflamed animal brains (Fernández et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data supported the attempt to use TH to overcome OPCs differentiation block during experimental inflammatory‐demyelinating diseases. Our previous work showed that a short in vivo TH administration during experimental allergic encephalomyelitis (EAE) promotes OPCs maturation, protects myelin sheaths and axons, and ultimately improves functional and clinical outcome in rat and non‐human primates Callithrix Jacchus (Calzà et al, ; Dell'Acqua et al, ; D'Intino et al, ; Fernández et al, ). TH supplementation also restores oligodendroglial lineage and OL maturation from neural stem/progenitor cells (NSCs) derived from inflamed animal brains (Fernández et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone (TH) is one of the best characterized differentiating agents of OPCs, inducing cell-cycle arrest and transcription of premyelinating genes (Billon et al, 2002;Casaccia-Bonnefil and Liu, 2003;Dugas et al, 2012). The circulating prohormone thyroxine (T4) secreted by the thyroid gland is converted into the active form (triiodothyronine, T3) by astrocytes in the CNS through the enzyme deiodinase 2 (D2) (Bianco et al, 2002;Calz a et al, 2015;Morte and Bernal, 2014). TH tissue homeostasis is then guaranteed by deiodinase 3 (D3), which inactivates T4 to reverse-T3 (rT3) and T3 to 3,5-diiodo-l-thyronine (T2).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the peripheral nerve fibers are vulnerable to be injured and hard to be healed in patients with T2DM. In the last decades, THs have been confirmed to be indispensable for the development of central nervous system (CNS) during fetal and neonatal periods and maintenance of CNS structure and function in adults [24]. Of note, among the THs, it is T3 rather than T4 the active form that specifically bind to the various thyroid receptors (TRs) to control a complex hierarchical cascade of target genes that may regulate the biological activities, such as initiating the expression of Kruppel-like factor 9, one of the myelination-associated genes [25].…”
Section: Discussionmentioning
confidence: 99%
“…Also, iodine deficiency causes an impaired maturation of hippocampal radial glial cells, which are involved in neuronal migration [66]. Specific alterations in dendritic morphology have been identified in the granule and pyramidal cells in the hippocampus due to TH deficiency [52,[65][66][67][68][69][70].…”
Section: Th Deficiency and Neuronal Developmentmentioning
confidence: 99%
“…Defects in synaptic architecture induced by TH insufficiencies, as well as deficiencies in protein substrates involved in complex signaling pathways serious for synaptic plasticity, culminate to disturb hippocampal neurophysiological function [67]. An irregular laminar distribution has been described in the auditory cortex of hypothyroid rats, including an increased number of neurons in layers V/VI, a concomitant diminution in layers II to IV, and the abnormal presence of neurons in the subcortical white matter [33,[69][70][71][72][73][74][75][76]. Finally, a reduction, or absence, of TH during brain maturation yields molecular, morphological and functional alterations in hippocampus [34,60,[74][75][76][77].…”
Section: Th Deficiency and Neuronal Developmentmentioning
confidence: 99%